2018
DOI: 10.1177/2055668318789280
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation therapy of patients with severe stroke based on functional electrical stimulation commanded by a brain computer interface

Abstract: Introduction Brain computer interface is an emerging technology to treat the sequelae of stroke. The purpose of this study was to explore the motor imagery related desynchronization of sensorimotor rhythms of stroke patients and to assess the efficacy of an upper limb neurorehabilitation therapy based on functional electrical stimulation controlled by a brain computer interface. Methods Eight severe chronic stroke patients were recruited. The study consisted of two stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 60 publications
2
44
0
1
Order By: Relevance
“…A total of 1015 records were screened, of which the full texts of 80 were assessed for eligibility. Finally, 33 studies were included in the current systematic review [6, 7, 15-17, 26, 35, 37, 46, 47, 49-71], of which 18 studies were of single-group design [26,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], and 15 studies were of controlled-trial design [6, 7, 15-17, 35, 46, 47, 49-55]. In the current review, only studies with a controlled-trial design were included in our metaanalysis, and those with single-group designs were only included in our qualitative description.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…A total of 1015 records were screened, of which the full texts of 80 were assessed for eligibility. Finally, 33 studies were included in the current systematic review [6, 7, 15-17, 26, 35, 37, 46, 47, 49-71], of which 18 studies were of single-group design [26,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], and 15 studies were of controlled-trial design [6, 7, 15-17, 35, 46, 47, 49-55]. In the current review, only studies with a controlled-trial design were included in our metaanalysis, and those with single-group designs were only included in our qualitative description.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…To clarify the spinal and cortical mechanisms related to visual and proprioceptive information, future studies should consider performing a detailed examination using TMS, peripheral nerve stimulation, and brain imaging methods. In addition, previous studies have suggested that therapy using motor imagery (Tabernig et al, 2018; Geiger et al, 2019) or vibration (Ahn et al, 2019; Toscano et al, 2019) could be beneficial in the neurorehabilitation of patients with stroke. Although we investigated whether the corticospinal excitabilities for reciprocal muscles were differentially affected by visuo-proprioceptive tasks, further studies should investigate whether engaging in combined observation and vibration can facilitate motor recovery of reciprocal muscles in patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 show the coefficient of determination r 2 distributed over topographical maps for the left and right sides, respectively. A threshold of 0.2 was defined to consider an r 2 value as significant; it was based on r 2 values from similar approaches [7], [19], [20], [39]. The right side had more significant differences between both groups than the left side for the flexion and extension MI tasks; there were no significant differences for the grasping MI task for both sides.…”
Section: A Bci Training Reinforcementmentioning
confidence: 99%
“…A brain-computer interface (BCI) can decode brain activity and translate motor intention to commands that can control devices; such as a computer [1], a virtual keyboard [2], an orthosis [3], [4], a functional electrical stimulator (FES) [5]- [7], and assistive robots [8]- [10]. Non-invasive methods record brain activity generally, such as electroencephalography (EEG); it is the most commonly adopted technology owing to be practical and affordable in comparison with other methods [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation